Analisis Tata Kelola Kebijakan Pelayanan Kesehatan dalam Meningkatkan Kualitas Layanan Publik di Kota Semarang - Ainun Ganisia; Karmanis Karmanis; Ruri Fintayana (Universitas 17 Agustus 1945 Semarang, Indonesia, 2026)
This study aims to analyze the governance of health service policies in improving the quality of public services in Semarang City. Health services are one of the essential sectors in public service delivery that require policies which are effective, transparent, and responsive to community needs. This research employs a qualitative approach with a descriptive method to understand the processes of policy formulation, implementation, and coordination among actors in the governance of health service policies. Data were collected through literature review, policy documentation, and analysis of health service delivery practices at the local government level. The results indicate that the governance of health service policies in Semarang City has undergone several improvement efforts through the strengthening of regulations, enhanced inter-agency coordination, and the utilization of health service innovations. However, several challenges remain, such as limited resources, inequality in service access, and the need to improve the quality of human resources in the health sector. Therefore, strengthening policy governance that is more collaborative, accountable, and community-oriented is necessary to sustainably improve the quality of health services. This study is expected to contribute to the development of public policy, particularly in the field of regional health service delivery.